2016
DOI: 10.1111/aos.12998
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 1.8‐mm incision versus 2.75‐mm incision cataract surgery in combined phacoemulsification and 23‐gauge vitrectomy

Abstract: ABSTRACT.Purpose: To compare 1.8 mm micro-incision and 2.75 mm standard incision in coaxial cataract surgery combined with 23-Gauge (23G) vitrectomy with respect to intraoperative and postoperative complications and outcomes. Methods: In this prospective study 30 eyes of 30 patients planned for combined phacoemulsification and 23G vitrectomy were enrolled, and randomized to undergo either Standard 2.75 mm Incision Cataract Surgery (SICS, 15 eyes) or Coaxial 1.8 mm Micro-Incision Cataract Surgery (C-MICS, 15 ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…However, in this study the 2.8 mm incision was used as the previous studies revealed no superiority for wound leakage between 2.8 and smaller incisions. 19,20…”
Section: Methodsmentioning
confidence: 99%
“…However, in this study the 2.8 mm incision was used as the previous studies revealed no superiority for wound leakage between 2.8 and smaller incisions. 19,20…”
Section: Methodsmentioning
confidence: 99%
“…In addition to an extra corneal incision, the intracameral approach could result in further iris trauma and pupil miosis and instability of anterior chamber, especially when using contact lenses visualization systems. [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, fear of surgery-associated intraocular inflammation has limited the clinical application of such treatment. Recently, there has been increasing progress in combined surgical techniques for cataract and pars plana vitrectomy surgeries, such as micro-incision cataract surgery combined with 23G or 25G sutureless vitrectomy (micro-incision vitrectomy (MIVS)) [ 2 4 ]. Besides, combined surgery has been complicated in eyes with uveitis [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%